Informing Responsible Investment Practices through Environmental, Social and Governance Analysis: A Perspective from South African Broad-Based Black Economic Empowerment and Transformation Disclosure - Taute, Delene Francis (Stellenbosch : Stellenbosch University, 2016)
Thesis (MPA)--Stellenbosch University, 2016.